Visualization of bubbles formation on the boiling process in tapering heat pipe with variation of evaporator to condenser diameter ratio - Sarip, Sarip; Soeparman, Sudjito; Yuliati, Lilis; Choiron, Moch. Agus (Eastern-European Journal of Enterprise Technologies, 2018)
In the present study, a new tapering heat pipe design had been developed to enhance the thermal performances. Boiling visualization in the tapering heat pipe is investigated to provide the detailed information of bubbles nucleation. Experiment was conducted in the tapering heat pipe with variation of the evaporator (d) to condenser (D) diameter ratio. The values of d/D are varied at 1/1; 1/2; 1/3 and 1/4. Heat load was generated at the evaporator section using heater DC-Power supply at 30, 40 and 50 Watt. The visualization technique was developed by using a transparent glass tube and the images of boiling bubbles were captured by SLR camera. The glass tube inclination is 45o and integrated with the NI-9211 and c-DAQ 9271 module. K-type thermocouple was set at the evaporator and condenser sections for measurement of boiling temperatures in the tapering heat pipe. Based on the results, it can be noted that variations of heat load and diameter ratio (d/D) of the evaporator and condenser affect the size and shape of boiling bubbles, as well as the nucleation temperature on the tapering heat pipe. The heat transfer coefficient tends to increase at a heat load of 50 W and diameter ratio d/D=1/4.